2009
DOI: 10.1111/j.1528-1167.2009.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the epidemiology of epilepsy in Arab countries

Abstract: Summary In this report the epidemiologic aspects of epilepsy in Arab countries are systematically reviewed. MEDLINE and Embase were searched, and six papers were identified: one incidence report from Qatar and five prevalence reports (two from Sudan, and one from each of Libya, Tunisia, and Saudi Arabia). An incidence of 174 per 100,000 persons in 2001 was reported in a hospital‐based study from Qatar. Prevalence ranged between 0.9/1,000 in Sudan and 6.5/1,000 in Saudi Arabia, with a median of 2.3/1,000. An ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
76
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 19 publications
7
76
3
1
Order By: Relevance
“…In our study, there was slight female preponderance which was statistically not significant, but is different from many of the epidemiological studies of epilepsy in Arab community 4,5,6 but has been reported from other parts of the world as one of the epidemiological study from Pakistan also showed slight female preponderance 9 and this female preponderance has also been reported from Nigeria 10 and Jordan.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, there was slight female preponderance which was statistically not significant, but is different from many of the epidemiological studies of epilepsy in Arab community 4,5,6 but has been reported from other parts of the world as one of the epidemiological study from Pakistan also showed slight female preponderance 9 and this female preponderance has also been reported from Nigeria 10 and Jordan.…”
Section: Resultscontrasting
confidence: 99%
“…6 Epidemiological studies about epilepsy from Arab countries especially Saudi Arabia are lacking. We were able to find only few studies about the prevalence of seizure disorder in an Arab population 5,7 and even sparser from Saudi Arabia. 4,8 we were unable to find any study regarding epidemiology of Epilepsy from our hospital.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Estimates of the prevalence and incidence of epilepsy worldwide vary considerably, likely reflecting differences in measurement and reporting, along with clinical characteristics such as etiology and seizure type. Previous systematic reviews of the prevalence of epilepsy focused on specific regions (China, 5 Europe, 6 Latin America, 7 and Arab countries 8 ) and prior reviews on the incidence of epilepsy did not use meta-analyses to explore associated factors. 9,10 Few of these studies explored potential sources of heterogeneity between estimates or they examined both prevalence and incidence globally.…”
mentioning
confidence: 99%
“…Patients with epilepsy are characterized by depression, anxiety, convulsions, and even loss of consciousness (Clancy et al 2014;Maguire et al 2014). Although efficient antiepileptic drugs and surgical procedures have improved during the past decade, these treatments are still unaffordable for most patients due to the high cost (Benamer & Grosset 2009;Newton & Garcia 2012;Beghi & Hesdorffer 2014). Furthermore, nearly all antiepileptic drugs have safety concerns and side effects (Malagon-Valdez 2004;Kaufman 2011), and an increasing number of patients are drug resistant (Noam et al 2013;Laxer et al 2014).…”
Section: Introductionmentioning
confidence: 99%